THE EFFECT OF DIGITAL CUSTOMER EXPERIENCE IN BY.U TOWARDS CUSTOMER BUYING DECISION - Nadissa Aliya Kadar, Karyn
The world evolves and so does our technology, shifting trend and behaviour changes amongst generations has led companies to innovate and provide new experiences to attract the customer’ hearts. In Indonesia, one of the biggest internet providers, Telkomsel, launched a new line of products named by.U. This new product serves as a new way of purchasing their products with an innovative digital customer experience. Through an application, the customer can buy the SIM card easily and customize their internet data package. This revolutionary way of digital customer experience is believed to lead to customer buying decisions. This research aims to identify the factors that influence the customer buying decision after experiencing by.U digital customer experience and give recommendations that can be implemented by by.U to create a better digital customer experience. The data was collected by interview and online questionnaire towards 355 by.U users and the quantitative data were analyzed through PLS-SEM to evaluate the relationship between the factors. The result shows that there are seven factors of digital customer experience in by.U. There are interactivity, connectivity, integration, security, consistency, personalization and product involvement. All of the factors except connectivity are positively affecting perception of innovation. Only perceived compatibility and perceived usefulness from the perception of innovation that leads to purchase intention and customer buying decision of by.U product. This research is providing some references for the improvement of marketing strategies towards digital customer experience. The insight of this research would help marketers by providing in-depth practical knowledge on how digital customer experience could increase the buying decision through perceived innovation characteristics and purchase intention. This research could be applied to digital internet provider to be able to understand its target market.